OPTIMALISASI PENGELOLAAN ZAKAT PRODUKTIF SEBAGAI REALISASI REVOLUSI MENTAL - Hasanah, Uswatun (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2020)
This research is based on the problem of poverty and unemployment. Poverty in Indonesia according to the Central Statistics Agency Report in September 2017 reached 26.58 million people. In Islam, poverty is a social responsibility that needs to be considered, one of which is through zakat. Zakat will be more meaningful if it increases economic empowerment for its recipients. For this reason, a mental revolution is needed for each element of zakat. Mental revolution is applied in the form of instilling the values of integrity, work ethic and mutual cooperation to the three elements of zakat namely muzakki, amil zakat and Mustahik. This research is a library research. Based on primary data sources and secondary sources. Data processing by editing, organizing, finding research results, analyzed and drawn conclusions. Through collecting data or scientific papers that aim with the object of research that is library. Research results show that with the mental revolution movement on the three elements of zakat, the welfare and independence of the people will be realized so that it will reduce poverty in Indonesia.